2021
DOI: 10.3390/e23091106
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Area Transport Equation for Bubble Coalescence and Breakup: Developments and Comparisons

Abstract: Bubble coalescence and breakup play important roles in physical-chemical processes and bubbles are treated in two groups in the interfacial area transport equation (IATE). This paper presents a review of IATE for bubble coalescence and breakup to model five bubble interaction mechanisms: bubble coalescence due to random collision, bubble coalescence due to wake entrainment, bubble breakup due to turbulent impact, bubble breakup due to shearing-off, and bubble breakup due to surface instability. In bubble coale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Thus, it caused the shallow depth of field (48 μm) and small observation area (4 × 4 mm 2 ); on the other hand, the microbubbles might be difficult to coalesce because of their own characteristics. The coalescence of bubbles was generally considered to be affected by the collision frequency and coalescence efficiency. In the absence of external force, the collision frequency of microbubbles was very low, causing difficulty for them to coalesce . However, the coalescence efficiency of microbubbles calculated by either the film drainage theory or the relative velocity theory was very high.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it caused the shallow depth of field (48 μm) and small observation area (4 × 4 mm 2 ); on the other hand, the microbubbles might be difficult to coalesce because of their own characteristics. The coalescence of bubbles was generally considered to be affected by the collision frequency and coalescence efficiency. In the absence of external force, the collision frequency of microbubbles was very low, causing difficulty for them to coalesce . However, the coalescence efficiency of microbubbles calculated by either the film drainage theory or the relative velocity theory was very high.…”
Section: Resultsmentioning
confidence: 99%
“…As for the motion of a single bubble in a multiphase system, it is essential for us to take full consideration on the coupling relationship in order to realize the unsteady coupling process [ 24 ]. Therefore, in this work, a coupled model is constructed with Fluent software (ANSYS Inc., Canonsburg, PA, USA) for the continuous phase and EDEM software (DEM Solutions Ltd., Edinburgh, UK) for the discrete phase, where the fluid and the bubble are discretized in the Eulerian and Lagrangian framework, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…(b) It has been identified that interfacial area transport equations (IATE) can handle all bubbles in two groups: the spherical/distorted bubble group and the cap/slug bubble group [ 38 , 39 , 40 ]. Moreover, 1 mm bubbles belong to Group I bubbles (spherical/distorted bubbles) in bubbly flow, which are treated in one-group IATE rather than two-group IATE [ 24 , 41 ]. Therefore, the coalescence and breakup of 1 mm bubbles are neglected in the dilute phase flow, and it is reasonable [ 24 ].…”
Section: Validation Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…The processes developing from the collisions of droplets [4,5] containing gas or vapor bubbles are comparable to the micro-explosive destruction of liquid [6,7]. However, in that case, the second phase in a water droplet emerges as a result of fast boiling liquid passing through a pipeline [8] and continuing its movement in a high-temperature gas medium [9]. Gas bubbles can also end up in liquid droplets when they collide during spraying [10].…”
Section: Introductionmentioning
confidence: 99%